PERAN PENDIDIKAN AGAMA ISLAM (PROSES PEMBELAJARAN) BAGI ANAK PENYANDANG AUTIS DI SEKOLAH INKLUSI SD IT ZAHIRA SCHOOL MEDAN - Oda Kinata Banurea (Universitas Islam Negeri Sumatera Utara Medan, 2017)
This study aims to reveal how big the role learning PAI for autistic children in school inclusion, in SD IT Zahira School Medan. In this research that became the outline of the issue is how the concept of Islamic religious education for persons with autism in school Inclusion Zahira School Medan. How the implementation of (the learning process) Islamic religious education for autistic children in school Zahira. What are the factors that support and hinder the implementation of Islamic religious education for autistic children in school Zahira terrain. The research was conducted using a descriptive qualitative approach. Engineering data collection done by observation the role (participant obcervation), in-depth interviews (indepth interview), documentation. Data analysis techniques by means of data processing and data analysis. Checking the credibility of the data using the persistence of observation, triangulation, peer, checking and checking of members. The results obtained from this research is all the components associated with the instructional Islamic education for autistic children should be tailored to the abilities and needs of an autistic child, including: (1) curriculum of Islamic education in schools inclusion in accordance with the public school curriculum, but the school inclusion is entitled to perform the modification. Learning methods and media that are used with customized material that is being taught, while the evaluation process the evaluation was done, post test and evaluation of the end of the semester. (2) the curriculum of Islamic religious education is a learning method, KTSP often used is the cermah, memorizing, faqs, group work, demonstrations and practice, while the media commonly used learning is visual media. The material taught includes Qur'an, aqidah, Fiqh, morals, and the date. (3) factor endowments: competent teachers, supervising teachers; the addition of the Islamic religious education lessons; facilities and infrastructure and the game can sharpen the brain. Factor inhibitor: an autistic concentration and mood often fickle